7b+12=7b+12

Simple and best practice solution for 7b+12=7b+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7b+12=7b+12 equation:


Simplifying
7b + 12 = 7b + 12

Reorder the terms:
12 + 7b = 7b + 12

Reorder the terms:
12 + 7b = 12 + 7b

Add '-12' to each side of the equation.
12 + -12 + 7b = 12 + -12 + 7b

Combine like terms: 12 + -12 = 0
0 + 7b = 12 + -12 + 7b
7b = 12 + -12 + 7b

Combine like terms: 12 + -12 = 0
7b = 0 + 7b
7b = 7b

Add '-7b' to each side of the equation.
7b + -7b = 7b + -7b

Combine like terms: 7b + -7b = 0
0 = 7b + -7b

Combine like terms: 7b + -7b = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5/x=0.86 | | 2x+5+2=3+12 | | -3x-12=-15 | | 4n^2-10=-11 | | 32y+6=1.2 | | 125+40x=225 | | 12x^2-5-11=0 | | 2x/16=(3x/4)-6 | | 3x-y+2x+4y= | | y/16=8 | | 9d-2d+4= | | -12y=2+y | | -74(d-3)=3 | | 18=9(y+6) | | (x^2-5x+6)=0 | | 3x/7=2x-3 | | 5x/8=9 | | 10x-50+14=36 | | -3x+19=6x+25 | | (3x/4-2) | | 4x-7(x-3)=-36 | | 2Y^2+15Y+10=0 | | 4x^3+5x^2=6-2x | | 4x+3=-6+2x | | 6x-(3-2x)=4-3(8-x) | | 8-3x-6=6.5 | | x+2x+64=148 | | 6.5(n-1)=-4 | | 125=5t^2+30t | | 35t=36 | | 2x-1/x=3 | | 7x+4y=68 |

Equations solver categories